Relationship between Knowledge and Attitude Towards Hypertension Incidents - Martha, Intan Puspita; Andora, Novika; Listina, Febria (Indonesian Journal of Global Health Research, 2024)
Hypertension is one of the chronic diseases that is a global health problem today because it is a disease with a high prevalence and continues to increase. The survey results found that most patients had low knowledge about hypertension and showed a less supportive attitude in the prevention and management of hypertension. The purpose of this study was to determine the relationship between knowledge and attitudes towards the incidence of hypertension at Clinic X Teluk Betung in 2024. This study is a quantitative study that uses the cross-sectional method. The sample in the study were patients who visited the Clinic X Teluk Betung, totaling 99 people using the purposive sampling technique. The research instrument was a questionnaire with data analysis using the Chi-Square test. The results of the analysis showed that the majority of research respondents had good knowledge as much as 95% and those who still had poor knowledge were 4%. As for the attitude category, the majority of respondents had an unfavorable attitude as much as 58.6% and those who had a good attitude were 41.4%. The Chi-Square test results obtained a p-value (0.626), which means that there is no relationship between the level of knowledge and the incidence of hypertension and has a 0.610 times chance of not having hypertension. And the p-value (0.016), which means there is a relationship between attitude and the incidence of hypertension in respondents with a good attitude and has a 0.346 times chance of not having a history of hypertension. We recommend that health counseling related to hypertension and hypertension prevention measures, especially factors that can cause hypertension, be increased again as an effort to prevent the incidence of hypertension.